International Prostate Symptom Score is a predictive factor of lower urinary tract symptoms after radical prostatectomy. (22nd January 2015) - Bayoud, Younes; de la Taille, Alexandre; Ouzzane, Adil; Ploussard, Guillaume; Allory, Yves; Yiou, René; Vordos, Dimitri; Hoznek, Andras; Salomon, Laurent
<x xml:space="preserve">Abstract</x> Objective To evaluate the impact of radical prostatectomy on lower urinary tract symptoms by using the International Prostate Symptom Score and International Prostate Symptom Score quality of life. Methods The present prospective study comprised 804 patients having localized prostate cancer who underwent radical prostatectomy. International Prostate Symptom Score and International Prostate Symptom Score quality of life were recorded preoperatively, and at 1, 3, 6, 12 and 24 months. Two study groups were considered: group 1 included patients with International Prostate Symptom Score ≤7 (mild) and group 2 included patients with International Prostate Symptom Score ≥8 (moderate to severe). Student's t‐test and logistic regression were carried out to detect a predictive factor of International Prostate Symptom Score ≤7 at 24 months. Results The mean International Prostate Symptom Score was 5.58 ± 6.6, 11.12 ± 7.1 and 7.62 ± 6 at baseline, 1 month and 3 months, respectively (P <0.0001). The mean quality of life score showed the same evolution with a significant difference at 1 and 3 months. The mean International Prostate Symptom Score was initially 1.57 ± 1.9 in group 1 and 13.51 ± 5.5 in group 2 (P <0.0001), evolving to 3.41 ± 3.1 and 7.69 ± 5.8 at 24 months (P <0.0001), respectively. The mean quality of life score was significantly different between the groups initially, and at 6 and 12 months with P <0.0001, P = 0.005 and P = 0.02, respectively. The multivariate logistic regression showed that age, prostate volume and preoperative International Prostate Symptom Score were independent predictive factors of International Prostate Symptom Score ≤7 at 24 months (P <0.0001). In group 2, 47 patients (17%) had an International Prostate Symptom Score ≥8 at 24 months, 15 of them (32%) having a QoL score ≥3. Conclusions The present study shows the beneficial impact of radical prostatectomy on lower urinary tract symptoms. However, a proportion of patients with a baseline International Prostate Symptom Score ≥8 maintain the same score at 24 months, with worsening in quality of life score in one‐third of them.